Clinical and computed tomography findings in Chinese lung cancer patients with HIV infection: A multi‐center study. Issue 3 (15th March 2017) - Cheng, Zenghui; Shan, Fei; Liu, Jinxin; Shi, Yuxin; Zhang, Zhiyong; Wu, Guowei
Abstract : Background: The study was conducted to investigate clinical and computed tomography (CT) features in Chinese lung cancer patients with human immunodeficiency virus (HIV). Methods: Forty consecutive lung cancer patients with HIV were included. Clinical data were collected, and CT features were reviewed and measured. The factors associated with stages of cancer and the CT features with opportunistic pulmonary infections (OPIs) were also analyzed. Results: Thirty‐four of the patients were men (85%), and the mean age was 57.5 years. The mean CD4 count was 288 cells/μL, and 23 patients received highly active antiretroviral therapy. OPIs were common (50%). The major histological type (85%) was non‐small cell lung cancer (NSCLC), and 15 NSCLC patients (44%) were in stages IIIb and IV. NSCLC patients with an OPI were more common in the advanced stages compared with those without an OPI ( P = 0.04). There were no significant differences in advanced and non‐advanced stages in terms of CD4 level, highly active antiretroviral therapy, and smoking ( P = 0.31, P = 1.00; P = 0.49, respectively). The average size of tumors was 4.5 cm. Irregularly shaped or larger sized tumors were associated with OPIs ( P = 0.03, P = 0.04, respectively). Conclusions: The persistence of locally irregular and large lesions in middle‐aged men with HIV and a history of OPIs should be an alert for lung cancer, and clinical management is needed.